Clinical Course and Surgical Outcomes of Patients with Tetralogy of Fallot with Absent Pulmonary Valve Syndrome: A Single-Center Retrospective Study - Şerif Şerifoğlu; Fatma Sevinç Şengül; Mustafa Nalbant; Buse Günyel; Yunus Emre Sarı; Mehmet Balcı; Pelin Ayyıldız; Aysel Türkvatan Cansever; Okan Yıldız; İsmihan Selen Onan; Sertaç Haydin; Alper Güzeltaş (Journal of Clinical Medicine, 2026)
Background: Tetralogy of Fallot with absent pulmonary valve syndrome (TOF-APVS) is a rare variant of tetralogy of Fallot marked by aneurysmal pulmonary artery dilatation and variable tracheobronchial compression. The identification of clinical indicators that predict perioperative risk in this patient population remains challenging. We aimed to review the surgical outcomes and reintervention requirements of patients with TOF-APVS over a 15-year single-center experience, with particular focus on two indicators of disease severity: preoperative mechanical ventilation (MV) and computed tomography (CT)-detected airway compression. Methods: We retrospectively reviewed 27 patients with TOF-APVS who underwent surgical repair at a single center between January 2010 and January 2025. Airway compression was assessed by CT in 20 patients. The primary outcome was the need for any reintervention during follow-up. Secondary outcomes comprised early and overall mortality and postoperative duration of intubation, ICU stay, and hospital stay. Subgroup comparisons were performed using the Fisher exact test and the Mann–Whitney U test. Results: The median age at surgery was 8 months (IQR, 4.5–16). Preoperative MV was required in 5 patients (18.5%), and CT revealed airway compression in 13 of 20 patients (65.0%). Early postoperative mortality was 7.4%, and overall mortality during follow-up was 18.5%. At least one reintervention was required in 9 patients (33.3%). Preoperative MV was significantly associated with early mortality (40.0% vs. 0%; p = 0.028) and with prolonged ICU stay (median 15 vs. 4 days; p = 0.008). CT-detected airway compression was not significantly associated with either mortality or reintervention. Conclusions: In this 15-year single-center experience with 27 patients, preoperative mechanical ventilation was associated with markedly higher early postoperative mortality and prolonged ICU stay, and may thus serve as a practical clinical indicator of disease severity in TOF-APVS. CT-detected airway compression was a frequent and often severe finding, but its association with early mortality and reintervention could not be statistically confirmed, likely reflecting the selective use of CT and small subgroup size. These findings support the integration of preoperative ventilation status into perioperative risk assessment and highlight the need for larger, preferably multicenter, studies with standardized airway assessment to clarify the prognostic role of anatomical airway compression.